Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's solve each inequality step-by-step and match each solution on the left side to the correct answer on the right side.
### Inequality 1: [tex]\(-9(x-1) \geq -3(x+5)\)[/tex]
First, we distribute the terms inside the parentheses:
[tex]\[ -9(x-1) \geq -3(x+5) \][/tex]
[tex]\[ -9x + 9 \geq -3x - 15 \][/tex]
Next, combine like terms to isolate [tex]\(x\)[/tex]:
[tex]\[ -9x + 9 + 3x \geq -3x - 15 + 3x \][/tex]
[tex]\[ -6x + 9 \geq -15 \][/tex]
Subtract 9 from both sides:
[tex]\[ -6x + 9 - 9 \geq -15 - 9 \][/tex]
[tex]\[ -6x \geq -24 \][/tex]
Divide by -6, and remember to reverse the inequality sign:
[tex]\[ x \leq 4 \][/tex]
### Inequality 2: [tex]\(\frac{2x+7}{5} \leq x-1\)[/tex]
Start by eliminating the fraction. Multiply both sides by 5:
[tex]\[ 2x + 7 \leq 5(x-1) \][/tex]
[tex]\[ 2x + 7 \leq 5x - 5 \][/tex]
Next, combine like terms to isolate [tex]\(x\)[/tex]:
[tex]\[ 2x + 7 - 2x \leq 5x - 5 - 2x \][/tex]
[tex]\[ 7 \leq 3x - 5 \][/tex]
Add 5 to both sides:
[tex]\[ 7 + 5 \leq 3x - 5 + 5 \][/tex]
[tex]\[ 12 \leq 3x \][/tex]
Divide by 3:
[tex]\[ 4 \leq x \][/tex]
Or:
[tex]\[ x \geq 4 \][/tex]
### Inequality 3: [tex]\(2(2x+7) \leq 6(x+2)\)[/tex]
Distribute the constants:
[tex]\[ 2(2x+7) \leq 6(x+2) \][/tex]
[tex]\[ 4x + 14 \leq 6x + 12 \][/tex]
Combine like terms to isolate [tex]\(x\)[/tex]:
[tex]\[ 4x + 14 - 4x \leq 6x + 12 - 4x \][/tex]
[tex]\[ 14 \leq 2x + 12 \][/tex]
Subtract 12 from both sides:
[tex]\[ 14 - 12 \leq 2x + 12 - 12 \][/tex]
[tex]\[ 2 \leq 2x \][/tex]
Divide by 2:
[tex]\[ 1 \leq x \][/tex]
Or:
[tex]\[ x \geq 1 \][/tex]
### Inequality 4: [tex]\(-3(2x-7) \geq -5(x-4)\)[/tex]
Distribute the constants:
[tex]\[ -3(2x-7) \geq -5(x-4) \][/tex]
[tex]\[ -6x + 21 \geq -5x + 20 \][/tex]
Combine like terms to isolate [tex]\(x\)[/tex]:
[tex]\[ -6x + 21 + 5x \geq -5x + 20 + 5x \][/tex]
[tex]\[ -x + 21 \geq 20 \][/tex]
Subtract 21 from both sides:
[tex]\[ -x + 21 - 21 \geq 20 - 21 \][/tex]
[tex]\[ -x \geq -1 \][/tex]
Divide by -1, and remember to reverse the inequality sign:
[tex]\[ x \leq 1 \][/tex]
### Matching the answers:
1. [tex]\(-9(x-1) \geq -3(x+5)\)[/tex] corresponds to [tex]\(x \leq 4\)[/tex].
2. [tex]\(\frac{2x+7}{5} \leq x-1\)[/tex] corresponds to [tex]\(x \geq 4\)[/tex].
3. [tex]\(2(2x+7) \leq 6(x+2)\)[/tex] corresponds to [tex]\(x \geq 1\)[/tex].
4. [tex]\(-3(2x-7) \geq -5(x-4)\)[/tex] corresponds to [tex]\(x \leq 1\)[/tex].
So, the final answers will be:
[tex]\[ \begin{array}{l} -9(x-1) \geq -3(x+5) \implies x \leq 4 \\ \frac{2x+7}{5} \leq x-1 \implies x \geq 4 \\ 2(2x+7) \leq 6(x+2) \implies x \geq 1 \\ -3(2x-7) \geq -5(x-4) \implies x \leq 1 \end{array} \][/tex]
### Inequality 1: [tex]\(-9(x-1) \geq -3(x+5)\)[/tex]
First, we distribute the terms inside the parentheses:
[tex]\[ -9(x-1) \geq -3(x+5) \][/tex]
[tex]\[ -9x + 9 \geq -3x - 15 \][/tex]
Next, combine like terms to isolate [tex]\(x\)[/tex]:
[tex]\[ -9x + 9 + 3x \geq -3x - 15 + 3x \][/tex]
[tex]\[ -6x + 9 \geq -15 \][/tex]
Subtract 9 from both sides:
[tex]\[ -6x + 9 - 9 \geq -15 - 9 \][/tex]
[tex]\[ -6x \geq -24 \][/tex]
Divide by -6, and remember to reverse the inequality sign:
[tex]\[ x \leq 4 \][/tex]
### Inequality 2: [tex]\(\frac{2x+7}{5} \leq x-1\)[/tex]
Start by eliminating the fraction. Multiply both sides by 5:
[tex]\[ 2x + 7 \leq 5(x-1) \][/tex]
[tex]\[ 2x + 7 \leq 5x - 5 \][/tex]
Next, combine like terms to isolate [tex]\(x\)[/tex]:
[tex]\[ 2x + 7 - 2x \leq 5x - 5 - 2x \][/tex]
[tex]\[ 7 \leq 3x - 5 \][/tex]
Add 5 to both sides:
[tex]\[ 7 + 5 \leq 3x - 5 + 5 \][/tex]
[tex]\[ 12 \leq 3x \][/tex]
Divide by 3:
[tex]\[ 4 \leq x \][/tex]
Or:
[tex]\[ x \geq 4 \][/tex]
### Inequality 3: [tex]\(2(2x+7) \leq 6(x+2)\)[/tex]
Distribute the constants:
[tex]\[ 2(2x+7) \leq 6(x+2) \][/tex]
[tex]\[ 4x + 14 \leq 6x + 12 \][/tex]
Combine like terms to isolate [tex]\(x\)[/tex]:
[tex]\[ 4x + 14 - 4x \leq 6x + 12 - 4x \][/tex]
[tex]\[ 14 \leq 2x + 12 \][/tex]
Subtract 12 from both sides:
[tex]\[ 14 - 12 \leq 2x + 12 - 12 \][/tex]
[tex]\[ 2 \leq 2x \][/tex]
Divide by 2:
[tex]\[ 1 \leq x \][/tex]
Or:
[tex]\[ x \geq 1 \][/tex]
### Inequality 4: [tex]\(-3(2x-7) \geq -5(x-4)\)[/tex]
Distribute the constants:
[tex]\[ -3(2x-7) \geq -5(x-4) \][/tex]
[tex]\[ -6x + 21 \geq -5x + 20 \][/tex]
Combine like terms to isolate [tex]\(x\)[/tex]:
[tex]\[ -6x + 21 + 5x \geq -5x + 20 + 5x \][/tex]
[tex]\[ -x + 21 \geq 20 \][/tex]
Subtract 21 from both sides:
[tex]\[ -x + 21 - 21 \geq 20 - 21 \][/tex]
[tex]\[ -x \geq -1 \][/tex]
Divide by -1, and remember to reverse the inequality sign:
[tex]\[ x \leq 1 \][/tex]
### Matching the answers:
1. [tex]\(-9(x-1) \geq -3(x+5)\)[/tex] corresponds to [tex]\(x \leq 4\)[/tex].
2. [tex]\(\frac{2x+7}{5} \leq x-1\)[/tex] corresponds to [tex]\(x \geq 4\)[/tex].
3. [tex]\(2(2x+7) \leq 6(x+2)\)[/tex] corresponds to [tex]\(x \geq 1\)[/tex].
4. [tex]\(-3(2x-7) \geq -5(x-4)\)[/tex] corresponds to [tex]\(x \leq 1\)[/tex].
So, the final answers will be:
[tex]\[ \begin{array}{l} -9(x-1) \geq -3(x+5) \implies x \leq 4 \\ \frac{2x+7}{5} \leq x-1 \implies x \geq 4 \\ 2(2x+7) \leq 6(x+2) \implies x \geq 1 \\ -3(2x-7) \geq -5(x-4) \implies x \leq 1 \end{array} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.